2019
DOI: 10.1111/cdev.13224
|View full text |Cite
|
Sign up to set email alerts
|

Secure Base Provision: A New Approach to Examining Links Between Maternal Caregiving and Infant Attachment

Abstract: This observational study addressed a critical gap in the understanding of the precursors of infant attachment by examining whether a new conceptualization of maternal caregiving behavior, secure base provision (SBP), explained variance in attachment above and beyond variance explained by sensitivity. Participants included 83 low‐socioeconomic status (SES), 4.5‐month‐old infants (56% male) and their mothers. Infant–mother dyads completed laboratory tasks at 4.5 months and three 30‐min home visits between 7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 43 publications
4
22
0
1
Order By: Relevance
“…This finding supports the idea that optimal caregiving may serve a protective function against adversities (Woodhouse, Scott, Hepworth, & Cassidy, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding supports the idea that optimal caregiving may serve a protective function against adversities (Woodhouse, Scott, Hepworth, & Cassidy, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Finally, an interaction between physical neglect and maternal parenting style on the overall Emotion Recognition Task score in healthy adults was observed, suggesting that optimal maternal parenting attenuates the negative impact of physical neglect on the ability to recognize emotions. This finding supports the idea that optimal caregiving may serve a protective function against adversities (Woodhouse, Scott, Hepworth, & Cassidy, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…This is in accordance with meta−analytic data, showing that sensitivity as originally defined by Ainsworth et al (1978) accounts for a low percentage of the variance in attachment—approximately 6% and only approximately 2% among families with low socioeconomic status ( Wolff and Van IJzendoorn, 1997 ). Relevant to our interest in physical contact and OT, Woodhouse et al (2020) recently demonstrated which of the many maternal behaviors measured via the sensitivity construct have the strongest impact on infant attachment outcomes. They found that among low SES mothers, it was their capacity to engage in ventral–ventral contact in order to soothe their distressed infants to a fully calm and regulated state at least 50% of the time as well as allow relatively uninterrupted exploration, which mattered the most.…”
Section: Extended Parent–infant Physical Contactmentioning
confidence: 99%
“…Currently, no longitudinal cross-generational human data exist for the maternal capacity to engage in extended or even brief but sufficiently long bouts of ventral–ventral physical contact (cf. Woodhouse et al, 2020 ). However, during the home observations that was part of the pioneering work of Ainsworth et al (1978) conducted to develop the Strange Situation for the assessment of infant attachment quality, some mothers were found to display aversion to physical contact stably across the first year of their childrens’ lives, with resultant infant aggression, conflict behavior, and ultimately insecure-avoidant attachment ( Main and Stadtman, 1981 ).…”
Section: Extended Parent–infant Physical Contactmentioning
confidence: 99%
“…As noted above, the quality of responsiveness that infants typically receive from their caregivers is believed to influence their attachment style (but note that infant temperament is believed to be a predictor too; see Belsky & Rovine, 1987; Goldsmith & Alansky, 1987). For example, securely attached infants are believed to have histories of high positive responsiveness, whereas insecurely attached infants are believed to have histories of lower or less consistent positive responsiveness (for a recent examination of what kinds of caregiving behaviors may or may not predict infant attachment security, see Woodhouse, Scott, Hepworth, & Cassidy, 2020).…”
Section: A Window Into How Infants Build Social Knowledgementioning
confidence: 99%